A human cell-based SARS-CoV-2 vaccine elicits potent neutralizing antibody responses and protects mice from SARS-CoV-2 challenge. Issue 1 (1st January 2021) - He, Xiangchuan; Ding, Longfei; Cao, Kangli; Peng, Haoran; Gu, Chenjian; Li, Yutang; Li, Duoduo; Dong, Lanlan; Hong, Xiujing; Wang, Xiangwei; Fu, Meilan; Qiu, Chenli; et al.
ABSTRACT: To curb the pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), multiple platforms have been employed toward a safe and highly effective vaccine. Here, we develop a novel cell-based vaccine candidate, namely K562-S, by utilizing human cell K562 as a cellular carrier to display Spike (S) protein of SARS-CoV-2 on the membrane. Analogous to the traditional inactivated vaccine, K562-S cells can be propagated to a large scale by culturing and completely lose their viability after exposure to X-ray irradiation or formalin. We in turn demonstrated high immunogenicity of formalin-inactivated K562-S vaccine in both mouse and non-human primates and its protective efficacy in mice. In mice, immunization with inactivated K562-S vaccines can elicit potent neutralizing antibody (nAb) responses persisting longer than 5 months. We consequently showed in a hACE2 mouse model of SARS-CoV-2 infection that a two-shot vaccination with adjuvanted K562-S rendered greater than 3 log reduction in viral lung load and concomitant ameliorated lung pathology. Of importance, the administration of the same regimen in non-human primates was able to induce a neutralizing antibody titer averaging three-fold higher relative to human convalescent serum. These results together support the promise of K562-based, S-protein-expressing vaccines as a novel vaccination approach against SARS-CoV-2. Importantly, with a powerful capacity to carry external genes for cell-based vectors, this platform could rapidly generate two- and multiple-valent vaccines by incorporating SARS-CoV-2 mutants, SARS-CoV, or MERS-CoV.